Macular perfusion velocities in the ocular ischaemic syndrome. Issue 1 (27th October 2018) - Klefter, Oliver Niels; Kofoed, Peter Kristian; Munch, Inger Christine; Larsen, Michael
Abstract: Purpose: To assess retinal perfusion in eyes with unilateral ocular ischaemic syndrome (OIS) and to compare with control subjects. Methods: Retrospective case series. Linear blood flow velocities in macular vessels were estimated using motion‐contrast fundus photography in eight patients with unilateral OIS (eight OIS eyes, seven fellow eyes) and 12 control subjects. The diagnosis of OIS was supported by carotid artery Doppler ultrasonography and pneumoplethysmographic measurement of ocular systolic perfusion pressure. Results: Macular arterial blood flow velocity (median, range) was 1.8 (1.4–2.7) mm/s in OIS eyes, 4.0 (2.9–5.3) mm/s in fellow eyes (p = 0.016) and 3.8 (2.3–5.1) mm/s in control eyes (p = 0.0004 and p = 0.67 versus OIS and fellow eyes, respectively). Macular venous blood flow velocity was 1.5 (1.0–2.1) mm/s in OIS eyes, 2.6 (2.0–2.9) mm/s in fellow eyes (p = 0.016) and 2.7 (1.8–3.5) mm/s in control eyes (p = 0.0007 and p = 0.64). Arterial velocities were below or equal to the lowest value observed in control subjects (≤2.3 mm/s) in seven of eight eyes with OIS. Visual acuity 0.7 or worse was found in two OIS eyes with arterial velocities below 1.7 mm/s and venous velocities below 1.3 mm/s and together with neovascular glaucoma or polycythemia vera (one eye each). Conclusion: Motion‐contrast imaging revealed markedly reduced macular perfusion velocities in OIS eyes compared with unaffected fellow eyes and healthy control eyes. The method appears to provide a clinically meaningful quantitative measure of macular hypoperfusion.